The Influencing Factors in Choosing the City of Fes as the Capital for the Idrisids Zahraa Saadoun Zajy - Zajy, Zahraa Saadoun (Thi Qar Arts Journal, 2024)
The Idrisids were the first Shia dynasty to reach power in the Islamic world. They succeeded in forming a strong government that exerted control over the West African region for three centuries. It is well-known that establishing any state requires finding a strong capital city as a base for that state. The choice of a city’s location is an important factor that plays an effective role in the stability and success of cities. Both external and internal factors, as well as geographical and environmental considerations, contribute to the success of these cities. For example, places located centrally, with infrastructure and fertile land, and close to civilization, tend to be more stable and successful.Fes, the capital of the Idrisids in the farthest part of Morocco, is one of the important capitals that was influenced by various factors leading to its success. Initially, the Idrisids resided in the city of Walili (Volubilis). Later, they moved to Fes, which was founded by Idris ibn Abdallah in the middle of the year 192 to 193 AH (Islamic calendar) in the farthest part of Morocco. Due to favorable geographical and strategic factors, the Idrisid rulers were able to govern effectively. Fes became a hub for scholars, traders, and a successful industrial zone.In this research, we explore the reasons that led Idris II to choose Fes as the capital, shifting it from Walili, and establish it as the capital of his state.